Child-Friendly learning media for inclusive schools: A systematic literature review - Candra Abdillah; Ani Rusilowati; Barokah Isdaryanti; Dameis Surya Anggara (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
This research aims to review child-friendly learning media that support inclusive school learning. The research method used is a systematic literature review (SLR) with a bibliometric approach. The data are in the form of search results for articles from various relevant Scopus sources. To find articles, researchers used five keywords in accordance with the PRISMA protocol. The article's source is the last 5 years (2019 - 2024). The number of articles analyzed was 84 Scopus-indexed articles. The results of the literature review explain (1) child-friendly learning media in inclusive schools include various types such as Gamification media for ADHD, PECS and SELFI for autistic students, multiliteracies-based online and social media platforms, and Machine Learning-based Media Augmentation (ML-MA) for accessible digital environments; (2) learning methods that support the application of teaching media such as differentiated instruction, collaborative learning, and the Universal Design for Learning (UDL); (3) The principles of implementing child-friendly teaching media prioritize child-centered, interactive, safe, developmentally appropriate, enhanced access, and accessibility. (4) The main obstacles in the implementation of this media are teachers' lack of understanding of the needs of children with disabilities, limited facilities, and a lack of professional training.